Potential Federal Regulation of Covenants to not Compete - Abigail Korrell (Bellarmine Law Society Review, 2020)
Korrell’s “Potential Federal Regulation of Covenants To Not Compete” outlines the past and present use of noncompete clauses, and highlights the problematic nature of inconsistent state employment laws. Invoking cases such as Application Group v. Hunter, Korrell argues for a more effective alternative: the national standardization of noncompete covenants law.